Nonoxidative dehydrogenation of methanol to methyl formate through highly stable and reusable CuMgO-based catalysts - Yuan D. J.; Hengne, A. M.; Saih, Y.; Huang, K. W. (ACS Omega, 2019)
Nonoxidative dehydrogenation of methanol to methyl formate over a CuMgO-based catalyst was investigated. Although the active site is metallic copper (Cu0), the best reaction conditions were obtained by tuning the ratio of Cu/Mg and doping the catalyst with 1 wt % of Pd to achieve a very specific activity for methyl formate synthesis. On the basis of the CO2 temperature-programmed desorption study, the basic strength of the catalyst plays a role in the efficient conversion of methanol to methyl formate via dehydrogenation. These CuMgO-based catalysts show excellent thermal stability during the reaction and the regeneration processes. Approx. 80% methanol conversion with constant selectivity to methyl formate was achieved even after 4 rounds of usage for a total reaction time exceeding 200 h, indicative of their potential for practical applications.